Comparative proteomics analysis between biofilm and planktonic cells of Mycobacterium tuberculosis. Issue 20 (6th June 2019) - Wang, Chao; Zhang, Qiaoli; Wang, Yang; Tang, Xudong; An, Yanan; Li, Shulin; Xu, Hongyue; Li, Yan; Luan, Wenjing; Wang, Xuefei; Liu, Mingyuan; Yu, Lu
Abstract: Tuberculosis is highly persistent and displays phenotypic resistance to high concentrations of antimicrobials. Recent reports exhibited that Mycobacterium tuberculosis biofilm was implicated to its pathogenicity and drug resistance. In this study, there were 47 kinds of differential proteins in the biofilm of M. tuberculosis H37Rv cells compared with the planktonic bacteria, and 37 proteins were nonredundant and identified by proteomics approach, such as 2DE and LC‐MS/MS. Moreover, six kinds of proteins were identified as HspX, which were conservative and highly expressed in biofilm. Note that 47 differential proteins were divided into seven categories, such as cell wall and cell processes, conserved hypotheticals, intermediary metabolism and respiration, and so on by TUBERCULIST. The Gene Ontology classification results showed that the largest protein group involved in metabolism, binding proteins, and catalytic function accounts for 30% and 57% of all identified proteins, respectively. Moreover, the protein interaction network analyzed by STRING showed that the minority proteins such as RpoA, SucC, Cbs, Tuf, DnaK, and GroeL in the interaction network have high network connectivity. These results implied that the proteins involved in metabolic process and catalytic function and the minority proteins mentioned above may play an important role in M. tuberculosis biofilm formation. To our knowledge, this is the first report about differential proteins between biofilm and planktonic M. tuberculosis, which provided the potential antigens for vaccines and target proteins for anti‐mycobacterial drugs.